Medico-legal responsibilities of the Malaysian medical graduate and the teaching of undergraduate forensic medicine - Paul, George; Murty, O.P. (Faculty of Medicine, University of Malaya, 1999)
The requirement of the medical graduate, tabled in the objectives of undergraduate medical education, as envisaged by the Malaysian Medical Council, call for the all round basic doctor to be able to handle any medical emergency, as well as meet the requirements of law in examining, documenting and reporting on the common offences of the Penal Code, where medical documentation is required of law for the purposes of dispensing justice. However, in tabling the amended requirements of the undergraduate syllabus on the lines of those followed in some of the more developed nations, we seem to have lost this perspective. The authors discuss, based on his previous experience from another former colonial country viz. India, where the objectives of the undergraduate training is the same, and the influences on the legal profession bear a common origin and governance, the relevance of some of these topics, coming under the ambit of Forensic Medicine and Toxicology as an undergraduate subject, in the day-'to-day practise of medicine in and out of government service. 'While this issue has been the frequent topic of discussion in international conferences and symposia, where the decline in the of medico-legal work in the countries attending have been blamed on the fall in the standard of undergraduate teaching, due recognition of the pitfalls of the deletion or whittling down of the course content, independent of the overall overhauling of the syllabi of medical schools, to keep up to the trends of overseas universities, has not been accorded in the planing of the course revisions, resulting in a deletion of a vital aspect of daily practise of medicine.